Crystal structure of highly glycosylated human leukocyte elastase in complex with an S2′ site binding inhibitor. Issue 8 (7th August 2018) - Hochscherf, Jennifer; Pietsch, Markus; Tieu, William; Kuan, Kevin; Abell, Andrew D.; Gütschow, Michael; Niefind, Karsten
Abstract : A novel binding mode of a small‐molecule inhibitor of human leukocyte elastase is revealed by its co‐crystal structure with the enzyme. In the structure, a comparatively large part of the N‐glycan chains attached to the enzyme are visible. Abstract : Glycosylated human leukocyte elastase (HLE) was crystallized and structurally analysed in complex with a 1, 3‐thiazolidine‐2, 4‐dione derivative that had been identified as an HLE inhibitor in preliminary studies. In contrast to previously described HLE structures with small‐molecule inhibitors, in this structure the inhibitor does not bind to the S1 and S2 substrate‐recognition sites; rather, this is the first HLE structure with a synthetic inhibitor in which the S2′ site is blocked that normally binds the second side chain at the C‐terminal side of the scissile peptide bond in a substrate protein. The inhibitor also induces the formation of crystalline HLE dimers that block access to the active sites and that are also predicted to be stable in solution. Neither such HLE dimers nor the corresponding crystal packing have been observed in previous HLE crystal structures. This novel crystalline environment contributes to the observation that comparatively large parts of the N‐glycan chains of HLE are defined by electron density. The final HLE structure contains the largest structurally defined carbohydrate trees among currently available HLE structures.